22.8k views
2 votes
please help me please help me please help me please help me please help me please help me please help me ​

please help me please help me please help me please help me please help me please-example-1
User MarioVilas
by
4.8k points

2 Answers

3 votes

Answer:

Explanation:

A >

Divide both side by sin^2 x , and we get

Subtracting cosec^2 x from both sides we get

B>lets break tan θ into its components tan θ = sin θ / cos θ and cot θ = 1/ tan θ

Tan θ + cot θ= Sin θ/cos θ + cos θ/ sin θ = sin^2 θ + cos^2 θ / sin θ cos θ= 1/ sin θ cos θ = sec θ cosec θ

User Schaka
by
5.5k points
1 vote

Answer:

See below

Explanation:

A >
Sin^(2) x + cos^(2) x = 1 \\

Divide both side by sin^2 x , and we get


(sin^2 x)/(sin^2 x) + (cos^2 x)/( sin^2 x) = (1)/(sin^2 x)


1+ cot^2 x= cosec^2 x

Subtracting cosec^2 x from both sides we get


Cosec^2 x - cot^2 x = 1

B>lets break tan θ into its components tan θ = sin θ / cos θ and cot θ = 1/ tan θ

Tan θ + cot θ= Sin θ/cos θ + cos θ/ sin θ = sin^2 θ + cos^2 θ / sin θ cos θ= 1/ sin θ cos θ = sec θ cosec θ

User Sebastien Bianchi
by
5.3k points